1995
DOI: 10.1116/1.588085
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum chemical vapor deposition with new gas phase pretreatment using tetrakisdimethylamino-titanium for ultralarge-scale integrated-circuit metallization

Abstract: A new gas phase pretreatment method was developed for blanket Al chemical vapor deposition ͑CVD͒ used in ultralarge-scale integration metallization. This method uses a halogen-free Ti compound.The pretreatment process involves exposing substrates to a tetrakisdimethylamino-titanium atmosphere before the Al CVD. This significantly lowers the deposition temperature of CVD using dimethylaluminum-hydride, and thus Al films can be deposited on SiO 2 even at 160°C, where deposition would otherwise not occur. The dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Aluminum thin films, especially those obtained via chemical vapor (CVD) or plasma-enhanced sputtering depositions have several properties that make them particularly attractive materials for use in advanced electronics fabrication. Among these are the low resistivity and high stability of the metal and low deposition temperatures. , Consequently, the surface chemistries of aluminum have been the focal point of much research. In order to fully understand the complex mechanisms of aluminum CVD, it is imperative that the elementary surface reaction mechanisms involving adsorbates bound to the surface of this metal be understood with the hope that these insights might help improve their efficiencies more generally. Additionally, the study of the interactions of hydrogen with metals is an area which has been afforded a great deal of attention due to its importance in understanding embrittlement. At least in part for these reasons, considerable effort has been put into studying the seemingly simple reactions of hydrogen with an aluminum single crystal surface. These studies have shown that this adsorbate system demonstrates remarkable properties, especially as regards the kinetics of hydrogen atom recombination on low-index single crystal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum thin films, especially those obtained via chemical vapor (CVD) or plasma-enhanced sputtering depositions have several properties that make them particularly attractive materials for use in advanced electronics fabrication. Among these are the low resistivity and high stability of the metal and low deposition temperatures. , Consequently, the surface chemistries of aluminum have been the focal point of much research. In order to fully understand the complex mechanisms of aluminum CVD, it is imperative that the elementary surface reaction mechanisms involving adsorbates bound to the surface of this metal be understood with the hope that these insights might help improve their efficiencies more generally. Additionally, the study of the interactions of hydrogen with metals is an area which has been afforded a great deal of attention due to its importance in understanding embrittlement. At least in part for these reasons, considerable effort has been put into studying the seemingly simple reactions of hydrogen with an aluminum single crystal surface. These studies have shown that this adsorbate system demonstrates remarkable properties, especially as regards the kinetics of hydrogen atom recombination on low-index single crystal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment sensitization is known to increase the density of island formation during the initial stages of aluminum plating. 20,21 For Ag plating, molecular dynamics studies on the adsorption of thin metallic layers, similar to the sensitization process, on silica surfaces can significantly change the bond character of the surface. 22 As a result, there can be a decrease in Si-O-Si bond angles on the silica surface.…”
Section: Effects Of Processing On Strengthmentioning
confidence: 99%
“…In plasma etching processes, the outcome is sensitive to a large number of factors including wafer temperature and etch species, and these factors affect the etch rate and etched features in complicated ways (1)(2)(3)(4). For example, etch selectivity was enhanced by adjusting the wall temperature since the surface loss probabilities of active species on the walls vary with temperature (3)(4)(5)(6). Moreover, the sticking coefficient of etching products that form a protecting film against etching on trench sidewall depends on the substrate temperature (4,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%